Differential Representation of Landmark and Self-Motion Information along the CA1 Radial Axis: Self-Motion Generated Place Fields Shift toward Landmarks during Septal Inactivation - Fattahi, Mohammad; Sharif, Farnaz; Geiller, Tristan; Royer, Sebastien (SOC NEUROSCIENCE, 2018)
Spatial location in the environment can be defined in relation to specific landmarks or in relation to the global context, and is estimated from both the sensing of landmarks and the inner sense of cumulated locomotion referred to as path-integration. The respective contribution of landmark and path-integration to place-cell activity in the hippocampus is still unclear and complicated by the fact that the two mechanisms usually overlap. To bias spatial mechanisms toward landmark or path-integration, we use a treadmill equipped with a long belt on which male mice run sequentially through a zone enriched and a zone impoverished in visual-tactile cues. We show that inactivation of the medial septum (MS), which is known to disrupt the periodic activity of grid cells, impairs mice ability to anticipate the delivery of a reward in the cue-impoverished zone and transiently alter the spatial configuration of place fields in the cue-impoverished zone selectively: following MS inactivation, place fields in the cue-impoverished zone progressively shift backward and stabilize near the cues, resulting in the contraction of the spatial representation around cues; following MS recovery, the initial spatial representation is progressively restored. Furthermore, we found that place fields in the cue-rich and cue-impoverished zones are preferentially generated by cells from the deep and superficial sublayers of CA1, respectively. These findings demonstrate with mechanistic insights the contribution of MS to the spread of spatial representations in cue-impoverished zones, and indicate a segregation of landmark-based and path-integration-assisted spatial mechanisms into deep and superficial CA1, respectively.
Keywords: MEDIAL ENTORHINAL CORTEX; HIPPOCAMPAL PYRAMIDAL CELLS; SHARP-WAVE RIPPLES; PATH-INTEGRATION; GRID CELLS; SPATIAL REPRESENTATION; VENTRAL HIPPOCAMPUS; NEURONS; ORGANIZATION; SEQUENCES